2020
DOI: 10.1002/ejlt.201900450
|View full text |Cite
|
Sign up to set email alerts
|

Tree Nut Oils: Chemical Profiles, Extraction, Stability, and Quality Concerns

Abstract: Tree nuts are globally consumed. Their kernels are calorie-rich, nutrient-dense foods and contain several bioactive and health-promoting components. While some nut crops have expanded through the world since ancient times (almond, hazelnut, walnut), more recently, there has been a parallel development of underexploited promising species (Brazil nut, macadamia, pecan). Nut kernels have high lipid content, ranging from 40% to 80% depending on nut species and varieties. In general, nut oils contain significant pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 118 publications
(281 reference statements)
3
37
0
1
Order By: Relevance
“…The bioactive substances in fruit seeds are described in Table 3. The total quantities of phytosterols were 1951.7, 3540.3, and 4565.7 mg kg -1 in mango, papaya, and mangaba seed oils, respectively, similarly to values found in some nuts for example almond, brazil nut, pecan, pistachio and walnut (Maestri et al, 2020). In all samples, β-sitosterol stood out among other phytosterols.…”
Section: Bioactive Compoundssupporting
confidence: 70%
See 3 more Smart Citations
“…The bioactive substances in fruit seeds are described in Table 3. The total quantities of phytosterols were 1951.7, 3540.3, and 4565.7 mg kg -1 in mango, papaya, and mangaba seed oils, respectively, similarly to values found in some nuts for example almond, brazil nut, pecan, pistachio and walnut (Maestri et al, 2020). In all samples, β-sitosterol stood out among other phytosterols.…”
Section: Bioactive Compoundssupporting
confidence: 70%
“…The amounts of total tocopherols were 14.37, 31.17, and 36.77 mg kg -1 in mango, papaya, and mangaba seed oils, respectively, similarly to macadamia oil (Maestri et al, 2020). These values are lower than what found in traditionally consumed oils such as corn (314-3116 mg kg -1 ), soybean (252-3627 mg kg -1 ), and sunflower (401-1021 mg kg -1 ) (Codex Alimentarius Commission, 2009).…”
Section: Bioactive Compoundsmentioning
confidence: 91%
See 2 more Smart Citations
“…Moisture content is one of the critical factors in nuts because it directly affects color, texture, rancidity, and shelf life. Maestri, Cittadini, Bodoira, and Martínez (2020) have investigated the effect of moisture content on nut tree oils. The study revealed that moisture content to be the most important factor influencing the onset of rancidity and high oil yields in nut kernels (Maestri et al, 2020).…”
Section: Moisture Contentmentioning
confidence: 99%